NOTES ON A COLLECTION OF DRAGONFLIES (ORDER ODONATA) FROM. THE DUTCH EAST INDIES AND DESCRIPTIONS OF FOUR NEW SPECIES FROM THE NEIGHBOURING CONTINENT - F. C. Fraser (BRIN Publishing (Penerbit BRIN), 1926)
-